2013
DOI: 10.1007/s10661-013-3367-0
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of dietary intakes of nineteen pesticide residues among five socioeconomic sections of Hyderabad—a total diet study approach

Abstract: Total diet study approach was used to assess the dietary intakes of pesticide residues among the select population in Hyderabad. When assessed by a food frequency questionnaire, it was found that the food intakes varied among five socioeconomic sections (SES). Therefore, we intended to compare the intakes of pesticide residues through these foods among the five SES. A total of 195 foods from different markets were collected and analyzed for 19 pesticides. The residues were analyzed with a gas chromatograph and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 19 publications
1
0
0
Order By: Relevance
“…The findings of dietary exposure estimation obtained in this study are in line with the estimated exposure reported from the Russia (3.10 ×10 -5 mg/kg bw/day for DDTs) (Polder et al, 2010), India (6.2 ×10 -6 mg/kg bw/day for dieldrin) (Betsy et al, 2014) and China (1.71×10 -5 for HCHs) (Zhang et al, 2017). However, the levels are comparatively higher than that from KPK-Pakistan (2.0×10 -5 mg/kg bw/day for DDTs) (Aamir et al, 2018), Cameron (2.7×10 -5 to 1.2×10 -5 mg/kg bw/day for cypermethrin) (Gimou et al, 2008) and Indonesia (4.0×10 -8 mg/kg bw/day for DDTs) (Shoiful et al, 2013) indicating higher health risks associated with the consumption of pesticides contaminated food available in the markets of Southern-Punjab, Pakistan.…”
Section: Estimation Of Pesticide Exposuresupporting
confidence: 90%
“…The findings of dietary exposure estimation obtained in this study are in line with the estimated exposure reported from the Russia (3.10 ×10 -5 mg/kg bw/day for DDTs) (Polder et al, 2010), India (6.2 ×10 -6 mg/kg bw/day for dieldrin) (Betsy et al, 2014) and China (1.71×10 -5 for HCHs) (Zhang et al, 2017). However, the levels are comparatively higher than that from KPK-Pakistan (2.0×10 -5 mg/kg bw/day for DDTs) (Aamir et al, 2018), Cameron (2.7×10 -5 to 1.2×10 -5 mg/kg bw/day for cypermethrin) (Gimou et al, 2008) and Indonesia (4.0×10 -8 mg/kg bw/day for DDTs) (Shoiful et al, 2013) indicating higher health risks associated with the consumption of pesticides contaminated food available in the markets of Southern-Punjab, Pakistan.…”
Section: Estimation Of Pesticide Exposuresupporting
confidence: 90%